Opening the black box of a sports-based programme for vulnerable youth: the crucial role of social bonds. Issue 3 (27th May 2018) - Moreau, Nicolas; Thibault Lévesque, Julien; Molgat, Marc; Jaimes, Annie; Parlavecchio, Luc; Chanteau, Olivier; Plante, Catherine
Abstract: While sports-based intervention programmes for youth attract much interest, little is known about the underlying processes that might account for their impact on participants. Moreover the perspectives of youths are seldom taken into account. The present article examines the underlying processes and key dimensions of sports-based interventions that contribute to the development of youth social bonds at the micro-social level. Such bonds are essential to reducing stigmatisation, discrimination and inequities. Our qualitative research presents a detailed case study on the sports intervention programme, DesÉquilibres . Results are based on the analysis of 27 interviews with participants, a focus group with 5 coaches and 'observant participation' of training sessions and challenges. We found that six elements are essential to DesÉquilibres : (1) Establishing a supportive climate; (2) Promoting collaborative strategies and group cooperation; (3) Striking a balance between outside rules and self-initiated actions; (4) Favouring collectivisation of individual performances; (5) Supporting the interconnectedness of effort and pleasure and (6) Exploring beyond participants' comfort zones. We conclude that certain conditions are necessary if the goals of sports programmes are to transform social bonds between youth, and between youth and coaches, in a positive and protective way.